Hilda Hilst and Georges Bataille Holding Hands with Death - Barbosa, Aline Leal Fernandes (2017)
The erotic, the sacred and death are recurrent themes in the works of Hilda Hilst and Georges Bataille. Betting on the continuous movement that transgresses the limits of what it means to be human, death, in its irrevocable character, will be the radical experience of continuity to which the erotic and the sacred tend, exemplifying the passage between animality and humanity. And since death is always that tertium quid, we intend in this article, based on the work and trajectory of Hilda Hilst and Georges Bataille, to outline some poetic landscapes about the spectacle of seeing oneself die through the other.